Design of robust superamphiphobic surfaces with enlarged area fractions: the considerable role of Laplace pressure in dynamics of contact lines. Issue 16 (6th April 2022) - Li, Yang; He, Yuting; Li, Jiaoyan; Lu, Chunhua; Ge, Haixiong; Xu, Zhongzi
Abstract : The considerable kinetic role of Laplace pressure in contact angles of superamphobic surfaces can be utilized for robust superamphibic surfaces with an enlarged area fraction via the narrow parallel channel design. Abstract : Superamphiphobic surfaces have attracted widespread attention because of their great potential for applications in biotechnology, optoelectronics, water/oil separation, etc. Re-entrant curvatures are widely reported to provide a metastable Cassie state for superamphiphobicity. For high contact angles, re-entrant surfaces with a small area fraction ( f ) are designed according to the Cassie equation. However, this will make the surfaces take high local pressures under a mechanical force and thus suffer from frangibility. Robustness and high repellency are seemingly mutually exclusive. Herein, contrary to Cassie's equation, we show that high contact angles (>150°) with a large f (69.4%) of water and oleic acid can be achieved by utilizing a large upward Laplace pressure with narrow and parallel channel geometries. We deeply studied the effect of Laplace pressure on superamphiphobicity and suppose that the larger upward Laplace pressure stops the droplet earlier and pins the contact line at a higher position, providing a higher contact angle. The similar effect of viscous force well supports our explanation. These findings enable us to obtain robust and durable superamphiphobic surfaces with an enlarged area fraction and simple re-entrant microstructures. Our work may open up design strategies for robust superamphiphobic surfaces with practical applications.